1999
DOI: 10.1046/j.1432-1327.1999.00522.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucose and deoxyglucose on the redistribution of calcium in Ehrlich ascites tumour and Zajdela hepatoma cells and its consequences for mitochondrial energetics

Abstract: The distribution of Ca 2+ in intact cells was monitored with fluorescent probes: fura-2 for cytosolic [Ca 2+ ] and rhod-2 for mitochondrial [Ca 2+ ]. It was found that in neoplastic cells, such as Ehrlich ascites tumour and Zajdela hepatoma, but not in non-malignant cells, such as fibroblasts, glucose and deoxyglucose elicited release of Ca 2+ from endoplasmic reticulum stores and an increase in Ca 2+ concentration in the cytosol. Parallel to this, a decrease in the rate of Ca 2+ extrusion from the cell and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 39 publications
1
28
1
1
Order By: Relevance
“…Various mechanisms have been suggested to explain the Crabtree effect in tumor cells: (a) competition between oxidative phosphorylation and glycolysis for ADP and inorganic phosphate (Sussman et al, 1980); (b) a decrease in the cytosolic pH, as a consequence of lactic acid formation, that diminishes the activity of oxidative enzymes (Heinz et al, 1981); (c) damage of the mitochondrial membranes by free radicals, produced as a consequence of glucose catabolism (Yang et al, 1997b); and (d) glucose-induced release of Ca 2+ from the endoplasmic reticulum followed by enhanced uptake of Ca 2+ by the mitochondria, which would inhibit ATP synthase (Wojtczak et al, 1999). The latter explanation would be in agreement with the observed elevation of the Ca 2+ content in tumor mitochondria.…”
Section: The Crabtree Effectmentioning
confidence: 99%
“…Various mechanisms have been suggested to explain the Crabtree effect in tumor cells: (a) competition between oxidative phosphorylation and glycolysis for ADP and inorganic phosphate (Sussman et al, 1980); (b) a decrease in the cytosolic pH, as a consequence of lactic acid formation, that diminishes the activity of oxidative enzymes (Heinz et al, 1981); (c) damage of the mitochondrial membranes by free radicals, produced as a consequence of glucose catabolism (Yang et al, 1997b); and (d) glucose-induced release of Ca 2+ from the endoplasmic reticulum followed by enhanced uptake of Ca 2+ by the mitochondria, which would inhibit ATP synthase (Wojtczak et al, 1999). The latter explanation would be in agreement with the observed elevation of the Ca 2+ content in tumor mitochondria.…”
Section: The Crabtree Effectmentioning
confidence: 99%
“…In Ehrlich ascites tumors and in Zajdela hepatoma cells, it has been observed that there is a glucose-induced increase in cytoplasmic calcium levels along with an enhanced mitochondrial uptake of this cation. Inside the mitochondria, Ca 2ϩ would inhibit ATP synthase by enhancing the interaction with IF1, its inhibitory subunit (16). However, is not clear whether this Ca 2ϩ accumulation is a common event in all Crabtree-positive cells, since in AS-D30 hepatoma cells, cal-cium levels are not modified after glucose addition (7).…”
mentioning
confidence: 99%
“…They are a principal energy source in these cells (1) and also are responsible for some mechanisms of apoptosis and necrosis (2-6) as well as for ischemic damage of tissues (4,(7)(8)(9)(10). Mitochondrial energy metabolism is very specific for cancer cells, which are characterized by the Crabtree effect (11)(12)(13)(14), by a very high hexokinase activity of mitochondria (15,16), and by high resistance to permeabilization of mitochondrial membranes by various pro-apoptotic proteins (2,(17)(18)(19)(20). Nevertheless some peptides have been found to be toxic for cancer cells (21)(22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%